Medical adhesive tape containing sepioteuthis lessoniana visceral polysaccharide and preparation method thereof
Patent Information
- Application Number
- CN202611059016.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-16
AI Technical Summary
[0008]本发明的目的在于提供一种含虎斑乌贼内脏多糖的医用胶带及其相关技术,以解决现有医用胶带抗氧化剂安全性差、稳定性不足、耐湿热性差、抗疲劳性不足等技术问题或其组合
(1)通过加速老化实验(70℃,168h)证明,添加0.3-0.5份虎斑乌贼内脏多糖的医用胶带,其180°剥离强度保留率可达95.6%-98.4%,显著优于未添加抗氧化剂的对照组(71.7%)和添加传统维生素C衍生物AA2G的对照组(91.6%)。这表明本发明的多糖具有更优的长效抗氧化稳定性。
Smart Images

Figure CN122542153B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medical adhesive products technology, specifically relating to a medical tape containing polysaccharide from the viscera of the tiger squid and its preparation method. Background Technology
[0002] Medical tapes are widely used to fix dressings, catheters, and instruments, requiring good adhesion, breathability, biocompatibility, and safety. Existing medical tapes typically use acrylic pressure-sensitive adhesive as the bonding layer. To prevent the adhesive layer from losing its stickiness due to oxidation during storage and use, antioxidants are often added. Commonly used antioxidants include synthetic phenols (such as BHT) and vitamin derivatives (such as vitamin C derivatives). However, synthetic phenolic antioxidants pose a risk of migration toxicity and are volatile, producing an irritating odor; vitamin derivatives are easily inactivated under light, heat, and oxygen conditions, and long-term contact may irritate the skin.
[0003] Tiger squid viscera, a waste product from food processing, is rich in polysaccharides, and studies have shown that they possess bioactivities such as antioxidant, anti-radiation, and wound-healing properties. However, there are currently no reports of using tiger squid viscera polysaccharides in medical acrylic pressure-sensitive tape.
[0004] Relevant patent documents retrieved: Chinese invention patent application CN109125114A discloses a hand cream containing cuttlefish viscera polysaccharide and its preparation method. The ingredients, by weight, are: 15-30 parts stearic acid, 2-5 parts glyceryl stearate, 5-8 parts cetyl alcohol, 15-30 parts glycerin, 5-10 parts white oil, 0.5-2 parts potassium hydroxide, 1-5 parts lavender essential oil, 0.1-0.3 parts sodium benzoate, 2-5 parts cuttlefish viscera polysaccharide, and 100 parts deionized water. The hand cream provided by this invention contains the natural active ingredient cuttlefish viscera polysaccharide, which can moisturize, repair wounds, resist radiation, and has antioxidant effects.
[0005] Relevant non-patent literature retrieved: The journal title is "Food Industry Technology", the article title is "Optimization of Extraction Process of Polysaccharide from Cuttlefish Viscera and Study on Antioxidant Activity and Moisture Absorption and Retention Properties by Response Surface Methodology", Volume 39, Issue 10, Publication Date: October 2018. This article discloses the extraction process of polysaccharide from cuttlefish viscera and its antioxidant activity and moisture absorption and retention properties.
[0006] The prior art represented by the aforementioned literature has at least the following unresolved technical problems or defects: Commonly used antioxidants in existing medical adhesive tapes, such as synthetic phenols (BHT), pose a risk of migration toxicity and are volatile, producing an irritating odor. Vitamin derivatives (such as AA2G) are easily deactivated under light, heat, and oxygen conditions, and prolonged contact may irritate sensitive skin. Meanwhile, acrylic pressure-sensitive adhesives readily absorb water and swell in the warm, humid environment of the human body, leading to adhesive layer structure breakdown, decreased adhesion, and affecting reliability and durability. Although squid visceral polysaccharides have been reported to possess antioxidant activity, no technical solution has yet been found that can simultaneously address multiple issues related to antioxidant properties, resistance to damp heat, fatigue resistance, and biocompatibility when applying them to medical pressure-sensitive adhesive tapes.
[0007] In solving the above problems or overcoming the above defects, the present invention encountered the following difficulties and obstacles: The visceral polysaccharide of the tiger squid is a heteropolysaccharide with significant differences in molecular size among its components. This difference directly affects its dispersibility and activity in pressure-sensitive adhesive systems, thus impacting the stability of the adhesive layer. Therefore, the selection of dialysis bags is crucial during the preparation process. Extensive experimentation is required to find the appropriate dialysis bag specifications that can screen out the effective components of the heteropolysaccharide. During the addition of the tiger squid visceral polysaccharide aqueous solution to the acrylic emulsion, it is necessary to find the right time to adjust the stirring speed to ensure uniform dispersion of the polysaccharide. Furthermore, the selection of the subsequent curing temperature must strike a balance between achieving the desired performance of the acrylic tape and preventing the functional groups of the polysaccharide from being destroyed and deactivated at high temperatures. Summary of the Invention
[0008] The purpose of this invention is to provide a medical tape containing polysaccharide from the viscera of the tiger squid and related technologies, so as to solve the technical problems of existing medical tapes, such as poor safety, insufficient stability, poor resistance to damp heat, and insufficient fatigue resistance, or combinations thereof.
[0009] Terminology Explanation: Unless otherwise defined, all technical terms used herein have the same meanings as commonly understood by one of ordinary skill in the art to which this subject matter pertains. Unless otherwise stated, all patents, patent inventions, and disclosures cited throughout this document are incorporated herein by reference in their entirety. Where multiple definitions exist for terms herein, the definitions provided in this chapter shall prevail.
[0010] It should be understood that the above brief description and the following detailed description are exemplary and for illustrative purposes only, and do not limit the subject matter of the invention in any way. In this invention, the singular is used in conjunction with the plural unless otherwise specifically stated. It should also be noted that, unless otherwise stated, the use of “or” or “or” means “and / or”. Furthermore, the use of the term “comprising” and other forms such as “including,” “containing,” and “contains” are not limiting.
[0011] Unless specifically defined herein, the use of all commercially available products herein employs standard techniques. For example, it may be carried out using the manufacturer's instructions for use with the kit, or in accordance with methods known in the art or the description of this invention. The techniques and methods described herein can generally be implemented according to conventional methods well known in the art, based on the descriptions in the various summary and more specific documents cited and discussed in this specification.
[0012] The terms “optional / arbitrary” or “optionally / arbitrarily” mean that the event or situation described below may or may not occur, including both the occurrence and non-occurrence of the event or situation.
[0013] The term "soft monomer" as used in this article refers to monomers with low glass transition temperatures in homopolymers, used to provide the adhesion and flexibility of pressure-sensitive adhesives, such as isooctyl acrylate and butyl acrylate.
[0014] The term "hard monomer" as used in this article refers to monomers with high glass transition temperatures in homopolymers, used to provide cohesive strength and temperature resistance in pressure-sensitive adhesives, such as methyl methacrylate and styrene.
[0015] The term "functional monomer" as used in this article refers to monomers containing active functional groups such as carboxyl and hydroxyl groups, which are used to provide cross-linking sites or enhance adhesion, such as acrylic acid, methacrylic acid, and hydroxyethyl acrylate.
[0016] The term “tiger squid viscera polysaccharide” used in this article refers to a natural polysaccharide extracted from the viscera of the tiger squid, which mainly contains pyranose-type dextran structures linked by α-glycosidic bonds and has multiple hydroxyl functional groups.
[0017] The term “swelling rate” as used in this article refers to the percentage increase in mass of the tape after it has been soaked in a buffer solution.
[0018] In a first aspect, the present invention provides a medical tape containing polysaccharide from the viscera of the tiger squid, comprising a substrate layer, a pressure-sensitive adhesive layer and a backing layer sequentially laminated together. The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 70-80 parts soft monomer, 10-15 parts hard monomer, 12-18 parts functional monomer, 0.2-0.5 parts initiator, 0.3-0.5 parts chain transfer agent, 0.3-0.5 parts squid viscera polysaccharide, 2-2.5 parts emulsifier, 0.1-0.3 parts foaming agent, 3-5 parts plasticizer, 1-2 parts antibacterial agent, 0.5-2 parts pH adjuster, and 30-70 parts water.
[0019] The soft monomer is selected from one or both of isooctyl acrylate and butyl acrylate; the hard monomer is selected from one or both of methyl methacrylate and styrene; the functional monomer is selected from one or more of acrylic acid, methacrylic acid, and hydroxyethyl acrylate; the initiator is ammonium persulfate; the chain transfer agent is dodecyl mercaptan; the emulsifier is STD-1 emulsifier; the foaming agent is azodicarbonamide; the plasticizer is glycerol; the antibacterial agent is nano zinc oxide; and the pH adjuster is ammonia.
[0020] The substrate layer is a PE release film or paper substrate with a thickness of 35-50 μm; the backing layer is a hot-air nonwoven fabric with a thickness of 250-350 μm or a cotton fabric with a thickness of 150-170 μm; the pressure-sensitive adhesive layer has a thickness of 200-300 μm and a dry adhesive coating amount of 18-20 g / m². 2 .
[0021] The preparation method of the tiger squid viscera polysaccharide includes: (1) The viscera of the tiger squid were washed, crushed into a homogenate, degreased by reflux with an organic solvent, freeze-dried and then pulverized to obtain dry powder of the viscera; (2) Extract the dried viscera powder with alkaline solution, centrifuge to obtain the supernatant, adjust the pH to neutral, concentrate and decolorize to obtain the decolorized solution; (3) Add chloroform-n-butanol mixture to the decolorizing solution, shake and centrifuge to remove the protein layer, and obtain supernatant a; (4) Add hydrogen peroxide solution to the supernatant a, keep it warm and then dialyze to obtain the dialysis concentrate; (5) Add ethanol solution to the dialysis concentrate, let stand, centrifuge, and dry to obtain the tiger squid viscera polysaccharide.
[0022] In step (1), the organic solvent is a mixture of C1-C2 alcohol and diethyl ether, wherein the C1-C2 alcohol is methanol or ethanol, the volume ratio of the C1-C2 alcohol to diethyl ether is 3:1, the reflux degreasing is performed 2-3 times, the amount of organic solvent used each time is 4-6 times the mass of the tiger squid viscera, the reflux temperature is 34-65℃, and the reflux time is 2-3h.
[0023] In step (2), the alkaline solution is a sodium hydroxide solution with a mass concentration of 5-15%, the mass-volume ratio of the dried viscera powder to the alkaline solution is 1g:10-20mL, the extraction temperature is 40-60℃, the extraction time is 2-3.5h, and the decolorization is performed by activated carbon adsorption, with the amount of activated carbon added being 1-3% of the mass of the concentrated solution.
[0024] In step (3), the volume ratio of the chloroform-n-butanol mixture is 4:1, the number of shaking times is 3-5, the shaking time is 20-40 min each time, and the amount of chloroform-n-butanol mixture used each time is 1-2 times the volume of the decolorizing liquid.
[0025] In step (4), the mass concentration of the hydrogen peroxide solution is 25-35%, the amount of hydrogen peroxide solution added is 0.3-0.5 times the volume of the supernatant a, the temperature for heat preservation is 35-45℃, and the heat preservation time is 3-5h; the dialysis uses a dialysis bag with a molecular weight cutoff of 1000-3500 Da, and the dialysis time is 20-28h.
[0026] The volume concentration of the ethanol solution in step (5) is 90-95%, the amount of ethanol solution added is 3-4 times the volume of the dialysis concentrate, the standing temperature is 2-6℃, and the standing time is 12-24h.
[0027] Based on further solutions to the technical problems of the present invention, or simultaneous solutions to multiple technical problems, the preferred solution in the technical solution provided in the first aspect of the present invention includes: The first preferred embodiment: The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 70-80 parts soft monomer, 10-15 parts hard monomer, 12-18 parts functional monomer, 0.2-0.5 parts initiator, 0.3-0.5 parts chain transfer agent, 0.3-0.5 parts squid viscera polysaccharide, 2-2.5 parts emulsifier, 0.1-0.3 parts foaming agent, 3-5 parts plasticizer, 1-2 parts antibacterial agent, 0.5-2 parts pH adjuster, and 30-70 parts water. This technical solution, while addressing the technical problem of "improving the safety of antioxidants," further solves the technical problems of "improving the peel strength retention rate after aging and inhibiting swelling."
[0028] The second preferred embodiment: the substrate layer is a PE release film or paper substrate with a thickness of 35-50μm; the backing layer is a hot-air nonwoven fabric with a thickness of 250-350μm or a cotton fabric with a thickness of 150-170μm; the pressure-sensitive adhesive layer has a thickness of 200-300μm and a dry adhesive coating amount of 18-20g / m². 2 This technical solution not only solved the technical problem of "ensuring the structural integrity of the tape", but also further solved the technical problem of "improving air permeability and flexibility".
[0029] Secondly, the present invention provides a method for preparing the above-mentioned medical tape containing the polysaccharide of the tiger squid viscera, comprising the following steps: S1. Mix soft monomers, hard monomers, functional monomers, emulsifiers and 25%-35% by weight of water, shear emulsify, then add initiators and chain transfer agents, keep warm and mature, adjust pH to obtain acrylic latex; S2. Mix the visceral polysaccharide of the tiger squid with the remaining water until homogeneous to obtain a visceral polysaccharide solution of the tiger squid; S3. Add the visceral polysaccharide solution of tiger squid to acrylic latex, stir, then mix with foaming agent and plasticizer, apply to the substrate layer, foam and mold, then composite with backing layer, and cure to obtain the final product.
[0030] In step S1, the rotation speed of shear emulsification is 9500-13000 rpm, the shear emulsification time is 25-35 min, the temperature of heat preservation and maturation is 60-75℃, the heat preservation and maturation time is 1.5-2.5 h, and the pH is adjusted to 6.5-7.5.
[0031] In step S3, the stirring speed is 300-500 rpm, the stirring time is 25-35 min, nitrogen gas is introduced during stirring, the ripening temperature is 35-45℃, and the ripening time is 20-28 h.
[0032] Polyacrylic acid (PAA) is rich in carboxyl groups (-COOH), which can act as strong hydrogen bond donors. The α-glycosidic pyranose structure of the glucan linked by the visceral polysaccharide of the tiger squid contains a large number of hydroxyl groups (-OH), which act as both hydrogen bond donors and acceptors. Therefore, under appropriate conditions, the carboxyl groups of PAA and the hydroxyl groups of glucan can form a cross-linked network through hydrogen bond interactions. Its function is as follows: ① The hydrogen bond network formed by the visceral polysaccharide of the tiger squid and polyacrylic acid (PAA) reduces the water absorption rate and degree by limiting the excessive extension of the acrylic polymer chain segments, thereby preventing structural disintegration failure caused by water absorption and swelling, and improving the tape's resistance to damp heat and long-term adhesion durability.
[0033] ② The visceral polysaccharide of the tiger squid, as a rigid polysaccharide skeleton, not only enhances the cross-linking density, but also provides an energy dissipation path under dynamic stress, which can significantly improve the fracture strength and fatigue peel resistance.
[0034] The present invention has at least the following beneficial effects: (1) Accelerated aging tests (70℃, 168h) demonstrated that medical tape with 0.3-0.5 parts of tiger squid viscera polysaccharide retained 95.6%-98.4% of its 180° peel strength, significantly better than the control group without antioxidants (71.7%) and the control group with traditional vitamin C derivative AA2G (91.6%). This indicates that the polysaccharide of the present invention has superior long-term antioxidant stability.
[0035] (2) After soaking in PBS buffer at 37°C for 24 hours, the swelling rate of pure acrylic pressure-sensitive tape was as high as 22%, and it cracked within 6 hours and was completely destroyed within 24 hours. In contrast, the swelling rate of the PAA-polysaccharide composite tape of the present invention was only 3.8%, and it maintained its structural integrity, did not delaminate, and did not disintegrate within 24 hours.
[0036] (3) In 500 consecutive 180° peel tests, the composite tape of the present invention maintained a peel strength retention rate of up to 87%, while the pure acrylic pressure-sensitive tape only maintained a retention rate of 65% after 500 cycles and exhibited cohesive failure. This indicates that the hydrogen bond crosslinking network provides an effective energy dissipation path, significantly improving the dynamic load capacity and reliability of the tape.
[0037] (4) The MTT cytotoxicity test conducted according to ISO 10993-5 showed that the cell survival rate of the composite tape of the present invention reached 89%, with a toxicity rating of Grade 1, while the cell survival rate of the pure acrylic pressure-sensitive tape was only 66%, with a rating of Grade 2. This demonstrates that the addition of polysaccharides significantly improves the biocompatibility of the tape and reduces the risk of skin irritation.
[0038] (5) In the test on detached pig skin simulating the human body's humid and hot environment (37°C, 90%RH, 168h), the peel strength retention rate of the composite tape of the present invention is as high as 90%, and there is no lifting, falling off, or residue; while the pure acrylic pressure-sensitive tape shows edge lifting within 80h, with a retention rate of only 71%. Attached Figure Description
[0039] Figure 1 This is a schematic diagram of the layered structure of the medical tape of the present invention. In the figure: 1-substrate layer (PE release film or paper substrate), 2-pressure sensitive adhesive layer (porous acrylic pressure sensitive adhesive), 3-backing layer (hot air nonwoven fabric or cotton fabric). Detailed Implementation
[0040] The following non-limiting embodiments are intended to enable those skilled in the art to gain a more comprehensive understanding of the present invention, but do not limit the invention in any way. The following content is merely an exemplary description of the scope of protection claimed by the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, and such changes should also fall within the scope of protection claimed by the present invention.
[0041] The present invention will be further described below by way of specific embodiments. Unless otherwise specified, all instruments, devices, equipment, reagents, products, etc., used in the embodiments of the present invention are obtained through conventional commercial means.
[0042] STD-1 emulsifier was purchased from Hubei Xingyan New Material Technology Co., Ltd.; nano zinc oxide (item number NO-O-002-1) was purchased from Shanghai Naio Nanotechnology Co., Ltd.
[0043] The preparation method of the tiger squid viscera polysaccharide is as follows: (1) Take fresh tiger squid viscera, remove the gonads, wash with running water and homogenize. Add ethanol-ether (3:1) mixture at a solid-liquid ratio of 1:5 and reflux twice to defatt the viscera. After filtration, freeze dry at -40℃ for 24 hours, pulverize and pass through an 80-mesh sieve to obtain dry viscera powder.
[0044] (2) Weigh out the dried viscera powder, add 8% NaOH solution (dried viscera powder: NaOH solution = 1g: 10mL), extract at 60℃ for 3h, centrifuge to take the supernatant, adjust the pH to 7.0, rotary evaporate to concentrate to 1 / 3 of the original volume, add 2% activated carbon by mass of the concentrate for decolorization and filtration.
[0045] (3) Add chloroform-n-butanol (4:1) to the filtrate at a volume ratio of 1:1, shake for 30 min, centrifuge at 4000 rpm for 15 min and discard the lower protein phase. Repeat 4 times. Add 0.4 times the volume of 30% H2O2 solution to the supernatant, incubate at 40℃ in the dark for 4 h, place in a dialysis bag with a molecular weight cutoff of 3000 Da, and dialyze with deionized water for 24 h.
[0046] (4) After the dialysate is concentrated, add 3 times the volume of 95% ethanol solution, let stand at 4℃ for 18h, centrifuge at 8000rpm to collect the white precipitate, and vacuum dry to obtain the tiger squid viscera polysaccharide.
[0047] Example 1 A medical tape containing polysaccharide from the viscera of the tiger squid is composed of a substrate layer, a pressure-sensitive adhesive layer, and a backing layer, laminated sequentially, as shown in the diagram. Figure 1 As shown.
[0048] The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 55 parts isooctyl acrylate, 20 parts butyl acrylate, 8 parts methyl methacrylate, 5 parts styrene, 5 parts acrylic acid, 5 parts methacrylic acid, 6 parts hydroxyethyl acrylate, 0.3 parts ammonium persulfate, 0.3 parts dodecyl mercaptan, 0.5 parts squid viscera polysaccharide, 2 parts STD-1 emulsifier, 0.2 parts azodicarbonamide, 4 parts medical grade glycerin, 1 part nano zinc oxide, 2 parts ammonia (25% by mass) and 60 parts water.
[0049] The preparation method of the above-mentioned medical tape containing polysaccharide from the viscera of the tiger squid is as follows: S1. Mix isooctyl acrylate, butyl acrylate, methyl methacrylate, styrene, acrylic acid, methacrylic acid, hydroxyethyl acrylate, STD-1 emulsifier, and 30% by weight of water. Shear emulsify at 12000 rpm for 30 min to obtain a pre-emulsion. Transfer the pre-emulsion to a reactor, heat to 75°C, add 1 / 3 of the ammonium persulfate solution (0.3 parts ammonium persulfate dissolved in 10 parts water), and then add the remaining ammonium persulfate solution dropwise over 4 h, adding dodecyl mercaptan in two portions during this period. Incubate for 2 h, adjust the pH to neutral with ammonia water to obtain acrylic latex.
[0050] S2. Mix the visceral polysaccharide of the tiger squid with the remaining water, adjust the pH to 6.5, and stir at 60°C until completely transparent to obtain a polysaccharide solution.
[0051] S3. Cool the acrylic latex to 48°C. Under nitrogen protection and stirring at 300 rpm, slowly add the polysaccharide solution dropwise to the acrylic latex and stir for 30 min. Then add azodicarbonamide, medical-grade glycerol, and nano zinc oxide, and mix thoroughly to obtain the mixture.
[0052] S4. Coat the above mixture onto a 40 μm thick single-sided corona-treated PE release film at a coating speed of 18 m / min and an adhesive content of 19 g / m. 2 The thickness is 0.2mm, foamed at 80℃, and then laminated with 65g / m³. 2 Hot air nonwoven fabric. The medical tape is obtained by allowing it to mature at a constant temperature of 40°C and 50% relative humidity for 24 hours.
[0053] Example 2 A medical tape containing polysaccharide from the viscera of the tiger squid is composed of a substrate layer, a pressure-sensitive adhesive layer, and a backing layer, which are sequentially laminated.
[0054] The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 50 parts isooctyl acrylate, 20 parts butyl acrylate, 8 parts methyl methacrylate, 5 parts styrene, 5 parts acrylic acid, 5 parts methacrylic acid, 6 parts hydroxyethyl acrylate, 0.28 parts ammonium persulfate, 0.25 parts dodecyl mercaptan, 0.4 parts squid viscera polysaccharide, 1.9 parts STD-1 emulsifier, 0.2 parts azodicarbonamide, 4 parts medical grade glycerin, 1 part nano zinc oxide, 2 parts ammonia (25% by mass) and 55 parts water.
[0055] The preparation method of the above-mentioned medical tape containing polysaccharide from the viscera of the tiger squid is as follows: S1. Mix isooctyl acrylate, butyl acrylate, methyl methacrylate, styrene, acrylic acid, methacrylic acid, hydroxyethyl acrylate, STD-1 emulsifier, and 30% by weight of water. Shear emulsify at 10,000 rpm for 30 min to obtain a pre-emulsion. Transfer the pre-emulsion to a reactor, heat to 75°C, add 1 / 3 of an ammonium persulfate solution (0.28 parts ammonium persulfate dissolved in 10 parts water), and then add the remaining ammonium persulfate solution dropwise over 4 h, adding dodecyl mercaptan in two portions during this period. Incubate for 2 h, adjust the pH to neutral with ammonia water to obtain acrylic latex.
[0056] S2. Mix the visceral polysaccharide of the tiger squid with the remaining water, adjust the pH to 6.5, and stir at 60°C until completely transparent.
[0057] S3. Cool the latex to 48°C. Under nitrogen protection and stirring at 300 rpm, slowly add the polysaccharide solution dropwise to the acrylic latex and stir for 30 minutes. Then add azodicarbonamide, medical-grade glycerin, and nano zinc oxide, and mix thoroughly.
[0058] S4. Coat the above mixture onto a 40 μm thick single-sided corona-treated PE release film at a coating speed of 18 m / min and an adhesive content of 19 g / m. 2 The thickness is 0.2mm, foamed at 80℃, and then laminated with 65g / m³. 2 Hot air nonwoven fabric. Medical tape is obtained by allowing it to mature at a constant temperature of 40°C and 50% relative humidity for 24 hours.
[0059] Example 3 A medical tape containing polysaccharide from the viscera of the tiger squid is composed of a substrate layer, a pressure-sensitive adhesive layer, and a backing layer, which are sequentially laminated.
[0060] The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 60 parts isooctyl acrylate, 20 parts butyl acrylate, 8 parts methyl methacrylate, 5 parts styrene, 5 parts acrylic acid, 5 parts methacrylic acid, 6 parts hydroxyethyl acrylate, 0.35 parts ammonium persulfate, 0.4 parts dodecyl mercaptan, 0.3 parts squid viscera polysaccharide, 2.2 parts STD-1 emulsifier, 0.2 parts azodicarbonamide, 4 parts medical grade glycerin, 1 part nano zinc oxide, 2 parts ammonia (25% by mass) and 50 parts water.
[0061] The preparation method of the above-mentioned medical tape containing polysaccharide from the viscera of the tiger squid is as follows: S1. Mix isooctyl acrylate, butyl acrylate, methyl methacrylate, styrene, acrylic acid, methacrylic acid, hydroxyethyl acrylate, STD-1 emulsifier, and 30% by weight of water. Shear emulsify at 13000 rpm for 30 min to obtain a pre-emulsion. Transfer the pre-emulsion to a reactor, heat to 75°C, add 1 / 3 of the ammonium persulfate solution (0.28 parts ammonium persulfate dissolved in 10 parts water), and then add the remaining ammonium persulfate solution dropwise over 4 h, adding dodecyl mercaptan in two portions during this period. Incubate for 2 h, adjust the pH to neutral with ammonia water to obtain acrylic latex.
[0062] S2. Mix the visceral polysaccharide of the tiger squid with the remaining water, adjust the pH to 6.5, and stir at 60°C until completely transparent.
[0063] S3. Cool the latex to 48°C. Under nitrogen protection and stirring at 300 rpm, slowly add the polysaccharide solution dropwise to the acrylic latex and stir for 30 minutes. Then add azodicarbonamide, medical-grade glycerin, and nano zinc oxide, and mix thoroughly.
[0064] S4. Coat the above mixture onto a 40 μm thick single-sided corona-treated PE release film at a coating speed of 18 m / min and an adhesive content of 19 g / m. 2 The material is 0.2 mm thick, foamed at 80℃, and then laminated with cotton fabric of 150-170 μm thickness. After being cured at a constant temperature of 40℃ and 50% relative humidity for 24 hours, medical tape is obtained.
[0065] Comparative Example 1 The only difference between this comparative example and Example 1 is that the tiger squid viscera polysaccharide is not added, and an equal amount of water is used instead.
[0066] Comparative Example 2 The only difference between this comparative example and Example 1 is that 0.5 parts of tiger squid viscera polysaccharide were replaced with 0.5 parts of vitamin C derivative AA2G.
[0067] Comparative Example 3 The only difference between this comparative example and Example 1 is that 0.5 parts of tiger squid visceral polysaccharide were replaced with 0.1 parts of tiger squid visceral polysaccharide.
[0068] Comparative Example 4 The difference between this comparative example and Example 1 is that 0.5 parts of tiger squid visceral polysaccharide were replaced with 0.7 parts of tiger squid visceral polysaccharide, and 60 parts of water were replaced with 70 parts.
[0069] Comparative Example 5 A chitosan-based medical tape comprises a substrate layer, a pressure-sensitive adhesive layer, and a backing layer sequentially laminated together, as shown in the following structure. Figure 1 As shown.
[0070] The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 55 parts isooctyl acrylate, 20 parts butyl acrylate, 8 parts methyl methacrylate, 5 parts styrene, 5 parts acrylic acid, 5 parts methacrylic acid, 6 parts hydroxyethyl acrylate, 0.3 parts ammonium persulfate, 0.3 parts dodecyl mercaptan, 0.5 parts chitosan (purchased from Shanxi Fenzhou Biotechnology Co., Ltd., item number: FZSW-357), 10 parts 50% polyacrylic acid aqueous solution (purchased from Guangdong Yuanxin Chemical Reagent Co., Ltd., item number: 10157689403052), 2 parts STD-1 emulsifier, 0.2 parts azodicarbonamide, 4 parts medical grade glycerin, 1 part nano zinc oxide, 2 parts ammonia, and 50 parts water.
[0071] The preparation method is as follows: S1. Mix isooctyl acrylate, butyl acrylate, methyl methacrylate, styrene, acrylic acid, methacrylic acid, hydroxyethyl acrylate, STD-1 emulsifier, and 30% water. Shear emulsify at 12000 rpm for 30 min to obtain a pre-emulsion. Transfer the pre-emulsion to a reactor, heat to 75℃, add 1 / 3 of the ammonium persulfate solution (0.3 parts ammonium persulfate dissolved in 10 parts water), then add the remaining ammonium persulfate solution dropwise over 4 h, adding dodecyl mercaptan in two portions during this period. Incubate for 2 h, adjust the pH to neutral with ammonia water to obtain acrylic latex.
[0072] S2. Mix chitosan with 10 parts of a 50% aqueous solution of polyacrylic acid, adjust the pH to 6.5, and stir at 60°C until completely transparent to obtain a chitosan solution.
[0073] S3. Cool the acrylic latex to 48°C. Under nitrogen protection and stirring at 300 rpm, slowly add the chitosan solution dropwise to the acrylic latex and stir for 30 min. Then add the remaining water, azodicarbonamide, medical-grade glycerol, and nano zinc oxide, and mix thoroughly to obtain the mixture.
[0074] S4. Coat the above mixture onto a 40 μm thick single-sided corona-treated PE release film at a coating speed of 18 m / min and an adhesive content of 19 g / m. 2 The thickness is 0.2mm, foamed at 80℃, and then laminated with 65g / m³. 2 Hot air nonwoven fabric. The medical tape is obtained by allowing it to mature at a constant temperature of 40°C and 50% relative humidity for 24 hours.
[0075] Comparative Example 6 A polyisobutylene pressure-sensitive adhesive tape containing visceral polysaccharide from tiger squid is composed of a substrate layer, a pressure-sensitive adhesive layer, and a backing layer sequentially laminated together, as shown in the following structure. Figure 1 As shown.
[0076] The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 22 parts of high molecular weight polyisobutylene (PIB) (purchased from Puyang Hengtai Petrochemical Co., Ltd., model: HM-80), 18 parts of low molecular weight polyisobutylene (PIB) (purchased from Shandong Hongrui New Material Technology Co., Ltd., model: HRD-13), 27.5 parts of amidated pectin (purchased from Zhejiang Guoyuan Kangpin Biotechnology Co., Ltd., model: high molecular weight amidated low ester pectin), 27.5 parts of carboxymethyl cellulose (CMC), 5 parts of potato starch (purchased from Sinek (Suzhou) Food Technology Co., Ltd., item number: 2548211), and 0.5 parts of tiger squid viscera polysaccharide.
[0077] The preparation method of the above-mentioned polyisobutylene pressure-sensitive adhesive tape containing tiger squid viscera polysaccharide is as follows: S1. High and low molecular weight PIB, amidated pectin, CMC, potato starch and tiger squid viscera polysaccharide are passed through a 120-mesh sieve to remove impurities. The above components are weighed according to the formula and preheated in a vacuum oven at 75℃ for 10 minutes for later use.
[0078] S2. First, add high-molecular-weight PIB to a Z-type mixer at 75℃ and 5kPa vacuum to soften for 20 minutes. Remove the vacuum, and add pectin, CMC, potato starch, and tiger squid viscera polysaccharide in sequence. Mix under normal pressure for 20 minutes until the material is uniform, and then degas at 75℃ and 5kPa vacuum for 20 minutes.
[0079] S3. Preheat the flat hot press mold to 75°C, put in the cured colloid, first pre-press with low pressure of 1.5kPa for 3min to exhaust the air, then increase the pressure to 8MPa and hold for 15min, and demold at constant temperature to obtain a 20μm thick colloid film.
[0080] The adhesive film was coated at 65 g / m at S4.75℃. 2 On a hot air nonwoven fabric, dry at a constant temperature of 75°C for 40 minutes. After drying, laminate a single-sided corona-electrode PE release film with a thickness of 40μm to obtain the above-mentioned polyisobutylene pressure-sensitive tape.
[0081] Effect test Test Example 1: Antioxidant Aging Test 1. Test material: Stainless steel plate, 2mm thick, Brinell hardness 130-200, surface polished.
[0082] 2. Sample Preparation: Take six tape samples from each of Examples 1-3 and Comparative Examples 1-6, grouping them into two groups, A and B, with a size of 25mm × 300mm. The backing film reinforcement material is 25μm transparent PET film. Remove the PE release film from the backing, attach the tape to a clean stainless steel plate, and roll it back and forth three times using a 2kg roller at a speed of 600mm / min. After attachment, allow it to stand at room temperature in a standard laboratory for 24 hours.
[0083] 3. Test Method: After standing for 24 hours, the peel strength of Group A samples was directly tested; Group B samples were placed in a constant temperature oven (70±2℃) and exposed to circulating air for 168 hours to simulate long-term oxidation. After reaching the standard test time, the samples were removed and placed in a standard laboratory environment at room temperature for 24 hours before peel strength testing. The peel angle was 180° and the speed was 300 mm / min. The appearance of the tape was observed, and the peel strength retention rate before and after aging was calculated.
[0084] 4. Test Results The test results are shown in Table 1.
[0085] Table 1 Results of Antioxidant Aging Test
[0086] The tape of Example 1, with 0.5 parts of tiger squid viscera polysaccharide added, retained a peel strength of up to 98.4% after aging; the tape of Example 2, with 0.3 parts of polysaccharide added, retained 96.7%, both significantly better than Comparative Example 1 (71.7%) without antioxidant. Compared with Comparative Example 2 (91.6%), which added the traditional antioxidant AA2G, the polysaccharide of the present invention also performed better. This indicates that tiger squid viscera polysaccharide has excellent antioxidant stability and can effectively protect the acrylic pressure-sensitive adhesive from tack degradation during long-term thermo-oxidative aging.
[0087] Test Example 2: Swelling Inhibition Experiment Medical adhesive tapes prepared in Examples 1-3 and Comparative Examples 1-6 were cut into standard square samples of 25mm × 25mm. The samples were kept to have uniform thickness and free of wrinkles or contamination. Three parallel samples were set up for each experiment to improve repeatability. The samples were dried in an electrically heated drying oven to constant weight, and the initial dry mass W was recorded. d .
[0088] Swelling environment setup: Inject PBS buffer into a container, place it in a constant temperature shaking water bath, and adjust the temperature to 37°C to simulate the human physiological environment.
[0089] Immersion and Sampling: Completely immerse the dried tape in PBS buffer for 24 hours. Remove the sample, gently blot away the surface liquid with filter paper, and quickly weigh its swollen mass W. s .
[0090] Swelling degree calculation: Calculated using the mass swelling ratio formula: Swelling degree (%) = (W s -W d ) / W d ×100%.
[0091] The experimental results are shown in Table 2.
[0092] Table 2 Results of swelling inhibition test
[0093] The average swelling rate of pure acrylic pressure-sensitive tape was 22%, and it cracked within 6 hours and completely disintegrated after 24 hours. In contrast, the average swelling rate of the PAA-polysaccharide composite tape of this invention was only 3.8%, and it maintained its structural integrity after 24 hours without significant delamination or disintegration. This indicates that a physical cross-linking network is formed between the visceral polysaccharide of the tiger squid and the polyacrylic acid through hydrogen bonds, significantly inhibiting the water absorption and swelling of the adhesive layer, thereby improving the structural stability and adhesion durability of the tape in humid and hot surface environments.
[0094] Test Example 3: 500 Cycle Adhesion Test Following the method described in Test Example 1, the tapes from Examples 1-3 and Comparative Examples 1-6 were subjected to a 180° peel strength test (peeling speed 300 mm / min) for 500 consecutive peels. The initial peel strength and the peel force after each cycle were recorded. Three parallel samples were used for each group, and the average value was taken. The test results are shown in Table 3.
[0095] Table 3 Adhesion test results
[0096] Test Example 4: Cytotoxicity Assay (MTT Method) Testing was conducted according to ISO 10993-5:2009 standard: (1) Preparation of extract: The tapes from Examples 1-3 and Comparative Examples 1-6 were cut into 2cm×3cm rectangles and sterilized with ethylene oxide. They were then incubated in serum-free MEM medium at a ratio of 6 cm² / mL at 37±1℃ in a sealed, light-protected environment for 24 hours, and then filtered through a 0.22μm filter membrane for sterilization. The positive control was a 0.64% phenol solution.
[0097] (2) Cell seeding: L-929 mouse fibroblasts were seeded at a dose of 1×10⁻⁶ cells / cells. 4 Cells were seeded at a density of 1 / mL in 96-well plates and cultured at 37°C with 5% CO2 until a monolayer adhered. No cells were seeded as a blank control.
[0098] (3) Adding samples: Change the culture medium, add sample extract to the experimental group, add equal amount of culture medium to the blank control and negative control, add equal amount of 0.64% phenol to the positive control, 5 replicates per group, and continue to culture for 72h.
[0099] (4) MTT assay: Add 15 μL of MTT solution to each well and incubate in the dark for 4 h. Discard the supernatant. Add 100 μL of DMSO to each well of the experimental group and the blank control group, and add an equal volume of culture medium to the negative control group. Shake for 10 min. Detect the OD values at 490 nm and 570 nm using a microplate reader.
[0100] (5) Calculate cell viability: Cell viability (%) = (OD 试验组 -OD 空白 ) / (OD 阴性 -OD 空白 )×100%.
[0101] The test results are shown in Table 4.
[0102] Table 4. Cytotoxicity test results
[0103] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.
Claims
1. A medical tape containing polysaccharide from the viscera of the tiger squid, characterized in that, It includes a substrate layer, a pressure-sensitive adhesive layer, and a backing layer that are laminated sequentially; The pressure-sensitive adhesive layer is prepared from the following raw materials in parts by weight: 70-80 parts soft monomer, 10-15 parts hard monomer, 12-18 parts functional monomer, 0.2-0.5 parts initiator, 0.3-0.5 parts chain transfer agent, 0.3-0.5 parts squid viscera polysaccharide, 2-2.5 parts emulsifier, 0.1-0.3 parts foaming agent, 3-5 parts plasticizer, 1-2 parts antibacterial agent, 0.5-2 parts pH adjuster, and 30-70 parts water; The functional monomer is composed of acrylic acid, methacrylic acid and hydroxyethyl acrylate; the soft monomer is selected from any one or two of isooctyl acrylate and butyl acrylate; the hard monomer is selected from any one or two of methyl methacrylate and styrene.
2. The medical tape according to claim 1, characterized in that, The initiator is ammonium persulfate; the chain transfer agent is dodecyl mercaptan; the emulsifier is STD-1 emulsifier; the foaming agent is azodicarbonamide; the plasticizer is glycerol; the antibacterial agent is nano zinc oxide; and the pH adjuster is ammonia.
3. The medical tape according to claim 1, characterized in that, The substrate layer is a PE release film or paper substrate with a thickness of 35-50 μm; the backing layer is a hot-air nonwoven fabric with a thickness of 250-350 μm or a cotton fabric with a thickness of 150-170 μm; the pressure-sensitive adhesive layer has a thickness of 200-300 μm and a dry adhesive coating amount of 18-20 g / m². 2 .
4. The medical tape according to claim 1, characterized in that, The preparation method of the tiger squid viscera polysaccharide includes: (1) The viscera of the tiger squid were washed, crushed into a homogenate, degreased by reflux with an organic solvent, freeze-dried and then pulverized to obtain dry powder of the viscera; (2) Extract the dried viscera powder with alkaline solution, centrifuge to obtain the supernatant, adjust the pH to neutral, concentrate and decolorize to obtain the decolorized solution; (3) Add chloroform-n-butanol mixture to the decolorizing solution, shake, centrifuge, and obtain supernatant a; (4) Add hydrogen peroxide solution to the supernatant a, keep it warm and then dialyze to obtain the dialysis concentrate; (5) Add ethanol solution to the dialysis concentrate, let stand, centrifuge, and dry to obtain the tiger squid viscera polysaccharide.
5. The medical tape according to claim 4, characterized in that, The organic solvent in step (1) is a mixture of C1-C2 alcohol and diethyl ether, wherein the C1-C2 alcohol is methanol or ethanol, the volume ratio of the C1-C2 alcohol to diethyl ether is 3:1, the reflux degreasing is performed 2-3 times, the amount of organic solvent used each time is 4-6 times the mass of the tiger squid viscera, the reflux temperature is 34-65℃, and the reflux time is 2-3h.
6. The medical tape according to claim 4, characterized in that, In step (2), the alkaline solution is a sodium hydroxide solution with a mass concentration of 5-15%. The mass-volume ratio of the dried viscera powder to the alkaline solution is 1g:10-20mL. The extraction temperature is 40-60℃ and the extraction time is 2-3.5h. The decolorization is performed by activated carbon adsorption, and the amount of activated carbon added is 1-3% of the mass of the concentrated solution. In step (3), the volume ratio of the chloroform-n-butanol mixture is 4:
1. The shaking is performed 3-5 times, and the shaking time is 20-40min each time. The amount of chloroform-n-butanol mixture used each time is 1-2 times the volume of the decolorization solution.
7. The medical tape according to claim 4, characterized in that, In step (4), the mass concentration of the hydrogen peroxide solution is 25-35%, the amount of hydrogen peroxide solution added is 0.3-0.5 times the volume of the supernatant a, the temperature for heat preservation is 35-45℃, and the heat preservation time is 3-5h; the dialysis uses a dialysis bag with a molecular weight cutoff of 1000-3500 Da, and the dialysis time is 20-28h; in step (5), the volume concentration of the ethanol solution is 90-95%, the amount of ethanol solution added is 3-4 times the volume of the dialysis concentrate, the temperature for standing is 2-6℃, and the standing time is 12-24h.
8. A method for preparing a medical tape containing visceral polysaccharide from tiger squid as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Mix soft monomers, hard monomers, functional monomers, emulsifiers and 25%-35% by weight of water, shear emulsify, then add initiators and chain transfer agents, keep warm and mature, adjust pH to obtain acrylic latex; S2. Mix the visceral polysaccharide of the tiger squid with the remaining water until homogeneous to obtain a visceral polysaccharide solution of the tiger squid; S3. Add the visceral polysaccharide solution of tiger squid to acrylic latex, stir, then mix with foaming agent and plasticizer, apply to the substrate layer, foam and mold, then composite with backing layer, and cure to obtain the final product.
9. The preparation method according to claim 8, characterized in that, In step S1, the rotation speed of shear emulsification is 9500-13000 rpm, the shear emulsification time is 25-35 min, the temperature of heat preservation and maturation is 60-75℃, the heat preservation and maturation time is 1.5-2.5 h, and the pH is adjusted to 6.5-7.
5.
10. The preparation method according to claim 8, characterized in that, In step S3, the stirring speed is 300-500 rpm, the stirring time is 25-35 min, nitrogen gas is introduced during stirring, the ripening temperature is 35-45℃, and the ripening time is 20-28 h.
Citation Information
Patent Citations
Sepiapharaonis visceral polysaccharide hand cream and preparation method thereof
CN109125114A
Negative electrode binder composition, negative electrode plate and secondary battery
CN119979064A
Pressure-sensitive adhesive containing nanocrystalline cellulose
US20170283669A1